2021
DOI: 10.2298/tsci180801163a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of flow and heat transfer in a porous medium between two stretchable disks using quasi-linearization method

Abstract: In this study, the flow as well as heat transfer of a classical Newtonian fluid of constant density and viscosity in a porous medium between two radially stretching disks is explored. The role of the porosity of the medium, the stretching of the disks, the viscous dissipation and radiation on the flow and temperature fields is taken into account. The flow and heat equations are transformed into nonlinear ordinary differential equations by invoking the classical similarity transformations. These nonlinear diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The Jalili et al 13 results showed that The average error between HAN method and HPM, for radial velocity is 3.1%, for axial velocity is 0.69%. Akhter et al 15 improved the studies that applied by Jalili et al 13 and Agarwal 14 with considering the porous medium for fluid flow. Hayat et al 16 used Jeffrey nanofluid between two rotating stretchable disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jalili et al 13 results showed that The average error between HAN method and HPM, for radial velocity is 3.1%, for axial velocity is 0.69%. Akhter et al 15 improved the studies that applied by Jalili et al 13 and Agarwal 14 with considering the porous medium for fluid flow. Hayat et al 16 used Jeffrey nanofluid between two rotating stretchable disks.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al 16 used Jeffrey nanofluid between two rotating stretchable disks. Compared to previous studies 1 15 , this innovation was the simultaneous rotation and expansion of two disks and the use of Jeffrey’s non-Newtonian nano-fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, wall shear stress and angular velocity gradient at the wall enhance with an enlargement in the material parameter as illustrated by Mandal and Mukhopadhyay [4]. Furthermore, the flow of MHD and heat transfer due to stretching rotating disk were examined by Mustafa [5] and Akhter et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Turkyilmazoglu [10] found the exact solution of micropolar fluid within the existence of the MHD effect. The MHD flow of micropolar fluids with a porous medium had been considered by many researchers, such as Sheikh et al [11], Akhter et al [12], Siddiq et al [13], Dero et al [14], Hayat et al [15,16], Ahmed et al [17], and Waqas et al [18].…”
Section: Introductionmentioning
confidence: 99%